1970
DOI: 10.13057/biodiv/d170138
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: Genetic identification of local pigs, and imported pigs Duroc) based on cytochrome b sequence analysis

Abstract: Hartatik T, Soewandi BDP, Volkandari SD, Tabun AC, Sumadi, Widodo. 2016. Genetic identification of local pigs, and imported pigs (Landrace and Duroc) based on cytochrome b sequence analysis. . The aim of this study was to identify the genetics of local pigs and imported pigs (Landrace and Duroc) based on qualitative analysis. Thirty-eight pigs were used in this study and consisted of 11 local pigs (from Bali), six Landrace pigs and four Duroc pigs (from Malang), nine Landrace pigs (from Bali) and eight local p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In mtDNA, the cytochrome b (cyt b) gene contains abundant phylogenetic information among intra-and interspecies and it is considered to be a good marker to study the genetic differentiation as well as phylogenetic relationships among species within the same genus or the same family (Browers et al 1994;Zardoya and Meyer 1996). The mtDNA has been proven to be useful markers for elucidating genetic diversity and relationships of domestic animals including chicken, goat, pig, horse, and cattle (Zhu et al 2014 Hartatik et al 2016;Sziszkosz et al 2016;Hartatik et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In mtDNA, the cytochrome b (cyt b) gene contains abundant phylogenetic information among intra-and interspecies and it is considered to be a good marker to study the genetic differentiation as well as phylogenetic relationships among species within the same genus or the same family (Browers et al 1994;Zardoya and Meyer 1996). The mtDNA has been proven to be useful markers for elucidating genetic diversity and relationships of domestic animals including chicken, goat, pig, horse, and cattle (Zhu et al 2014 Hartatik et al 2016;Sziszkosz et al 2016;Hartatik et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, according to the Domestic Animal Diversity Information System (FAO, http://fao.org/dad-is), the Mong Cai breed shares characteristics with Luchuan pigs, native to China's Guangxi Province (Pham et al 2014;Bui et al 2018). Other evidence from mtDNA and microsatellite studies also revealed that the Mong Cai pig and Vietnamese indigenous pig breeds have a close genetic relationship with Asian pig breeds regarding maternal lineage and are grouped into a separate branch from European breeds (Hartatik et al 2016;Bui et al 2018).…”
Section: Origin Of Mong Cai Breedmentioning
confidence: 95%